MR imaging tracking of inflammation-activatable engineered neutrophils for targeted therapy of surgically treated glioma. Issue 1 (December 2018) - Wu, Meiying; Zhang, Haixian; Tie, Changjun; Yan, Chunhong; Deng, Zhiting; Wan, Qian; Liu, Xin; Yan, Fei; Zheng, Hairong
Abstract Cell-based drug delivery systems have shown promising capability for tumor-targeted therapy owing to the intrinsic tumor-homing and drug-carrying property of some living cells. However, imaging tracking of their migration and bio-effects is urgently needed for clinical application, especially for glioma. Here, we report the inflammation-activatable engineered neutrophils by internalizing doxorubicin-loaded magnetic mesoporous silica nanoparticles (ND-MMSNs) which can provide the potential for magnetic resonance (MR) imaging tracking of the drug-loaded cells to actively target inflamed brain tumor after surgical resection of primary tumor. The phagocytized D-MMSNs possess high drug loading efficiency and do not affect the host neutrophils' viability, thus remarkably improving intratumoral drug concentration and delaying relapse of surgically treated glioma. Our study offers a new strategy in targeted cancer theranostics through combining the merits of living cells and nanoparticle carriers. Imaging tracking of the migration of cell-based drug delivery systems are needed for expanding their clinical application for glioma. Here they report inflammation activatable engineered neutrophils containing doxorubicin-loaded magnetic mesoporous silica nanoparticles to image and actively target brain tumors after resection.